Bacteriocins active against plant pathogenic bacteria. (21st November 2012) - Grinter, Rhys; Milner, Joel; Walker, Daniel
Abstract : Gram-negative phytopathogens cause significant losses in a diverse range of economically important crop plants. The effectiveness of traditional countermeasures, such as the breeding and introduction of resistant cultivars, is often limited by the dearth of available sources of genetic resistance. An alternative strategy to reduce loss to specific bacterial phytopathogens is to use narrow-spectrum protein antibiotics such as colicin-like bacteriocins as biocontrol agents. A number of colicin-like bacteriocins active against phytopathogenic bacteria have been described previously as have strategies for their application to biocontrol. In the present paper, we discuss these strategies and our own recent work on the identification and characterization of candidate bacteriocins and how these potent and selective antimicrobial agents can be effectively applied to the control of economically important plant disease.